Experimental study on dynamic filtration behavior of liquid CO2 in tight sandstone. (15th August 2018) - Li, Binfei; Zheng, Chao; Xu, Jianguo; Lv, Qichao; Shi, Dashan; Li, Zhaomin
Abstract: Liquid carbon dioxide (CO2 ) fracturing can not only enhance oil and gas production efficiently, but also realize resource utilization of CO2 . Moreover, it has great potential in unconventional oil and gas exploration, as well as in carbon utilization and storage. In this study, the filtration performance of liquid CO2 in tight sandstone was studied, and the effects of CO2 temperature, pressure, thickener concentration, phase change, the oil in the formation on CO2 filtration characteristics were systematically analyzed. The results show that the viscosity is the main factor affecting the filtration rate when there is no change in the CO2 phase state. With the rise in the temperature or decline in the pressure, the viscosity of CO2 decreases and the CO2 filtration coefficient increases. Thickener added to CO2 can effectively control the filtration velocity of CO2 . The filtration coefficient of CO2 with thickener decreases by one order of magnitude compared to that of pure CO2 . The oil in the formation significantly lower the CO2 filtration by one order of magnitude, and it decreases with the rise of the oil viscosity. The phase change of CO2 dramatically affects the filtration. When CO2 is transforming from liquid to supercritical state in formation, the effect of two phase flow and volume expansion significantly decrease the filtration velocity. According this study, the dynamic filtration behavior of liquid CO2 in tight sandstone has been obtained. The results provide the basic data to the application of liquid CO2 fracturing and CO2 injection in CCUS.